Introduction to Access and Benefit-Sharing and the Nagoya Protocol: What DNA Barcoding Researchers Need to Know - Alex Borisenko (Pensoft Publishers, 2017)
The Global Taxonomy Initiative has provided training opportunities for Parties to apply DNA-sequence based species identification method as a tool for biodiversity management that requires rapid species identification. The method of DNA barcoding has invigorated taxonomic research and is now applied in a wide range of areas, including environmental assessment, food inspection, disease control and public education. DNA barcoding has proven to be a powerful tool for both taxonomists and all biodiversity stakeholders, including women and children, and indigenous peoples and local communities. On the other hand, DNA barcoding practices have raised concerns among the public. These concerns include expatriation of biological specimens, sharing of digital sequence information and associated data with potential value, risks of unapproved changes of research purpose or benefits to be shared. This e-book provides practical advice on international collaborations that comply with the Nagoya Protocol and relevant national laws and regulations.